A educação socioemocional para além da BNCC: uma análise das produções acadêmicas e suas contribuições para uma formação integral - Souza, Élica dos Santos (Universidade Federal de São Carlos, 2025)
This doctoral thesis was developed in the Graduate Program in Education (PPGE) at the Federal University of São Carlos (UFSCar) in the research area of Education, Culture, and Subjectivity, and is also the result of discussions and studies by the Research Group on Compassion Science and Education. We seek to analyze the following issues: How does the National Common Core Curriculum (BNCC) incorporate this issue? How do critics of the social-emotional education present in the BNCC present their arguments? And also, how can we think about social-emotional education that goes beyond the debate generated by the BNCC? Thus, our hypothesis is that the BNCC includes social-emotional education in a restricted and superficial manner, aligned with a technical and instrumental approach. The general objective is to analyze how social-emotional education has been presented within the scope of the BNCC, in order to also highlight how its critics have constructed their arguments against it. The methodology used to develop the research problem and objectives was theoretical and bibliographic research. First, we surveyed 19 articles available on the Capes Journal Portal, published between 2018 and 2022. We selected the year 2018 because it marked the approval and beginning of the implementation of the BNCC in schools. These studies address both the historical context of its construction and implementation and the appropriation of social-emotional learning in the Brazilian context. In addition, we conducted a second data search in the Web of Science database, between 2020 and 2024, with the aim of identifying more recent research. From this selection, we obtained 23 meta-analysis articles that investigate international social-emotional learning programs and strategies, highlighting effective results for both teaching and student learning. Thus, in our analysis, we were able to understand that social-emotional learning is seen in the 19 articles as the preparation and inclusion of students for the job market and that the business environment has a significant influence on both the BNCC and the introduction of social-emotional learning in Brazil. The 23 meta-analysis studies reviewed indicate that the concept of social-emotional learning adopted in several countries is broad, contextualized, and multidimensional, contrasting with the BNCC approach, which is more restrictive, technical, and prescriptive. Furthermore, there is a lack of clear guidelines in the Base regarding the teacher training necessary for a critical and contextualized practice of social-emotional learning. Thus, ideal social-emotional learning is focused on training conscious individuals who are capable of acting on reality and contributing to the construction of a more just, humane, and supportive society.
Social-emotional learning beyond the BNCC: an analysis of academic publications and their contributions to comprehensive education
Keywords: Educação socioemocional; BNCC; Formação Integral; Socio-emotional learning; BNCC; Holistic education; CIENCIAS HUMANAS::EDUCACAO